2012
DOI: 10.1007/s00704-011-0582-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Madden–Julian Oscillation in the genesis of North Indian Ocean tropical cyclones

Abstract: Cyclonic storms having maximum winds of 34 knots and above that had genesis in north Indian Ocean have been studied with respect to the eastward passage of Madden-Julian Oscillation (MJO). In the three decades , there were a total of 118 cyclones reported in which 96 formed in the region chosen (0-15 o N, 60 o E-100 o E) for the study. Although the percentage of MJO days inducing cyclogenesis is small, it is found that tropical cyclone genesis preferentially occurred during the convective phase of MJO. This ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Gray 1979) are present in the BoB during the pre-monsoon season, TCs do not arise simply because these conditions are met (Riehl 1950;Bergeron 1954). Additional forcing such as ISO is needed to trigger tropical cyclogenesis (Emanuel 2003;Krishnamohan et al 2012). As was pointed out by Kikuchi and Wang (2010), about 60% of TCs that form over the Indian Ocean do so in association with significant ISO events.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gray 1979) are present in the BoB during the pre-monsoon season, TCs do not arise simply because these conditions are met (Riehl 1950;Bergeron 1954). Additional forcing such as ISO is needed to trigger tropical cyclogenesis (Emanuel 2003;Krishnamohan et al 2012). As was pointed out by Kikuchi and Wang (2010), about 60% of TCs that form over the Indian Ocean do so in association with significant ISO events.…”
Section: Introductionmentioning
confidence: 95%
“…The MJO constantly interacts with the underlying ocean and influences many weather and climate systems (Zhang 2005). In the tropics, the MJO modifies the large-scale circulation anomalies conducive for TC development; this is the case in the BoB (Krishnamohan 2012;Kikuchi and Wang 2010). During the positive phase of the MJO (based upon convergence over the Indian Ocean-western Pacific region), synoptic conditions that are favorable for TC development are considerably enhanced (Maloney and Hartmann 2000;Bessafi and Wheeler 2006;Ho et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kikuchi and Wang (2010) found that north Indian TC development was favored when convection was enhanced over the Malay Peninsula and dry conditions were present over most of the Indian Ocean. Krishnamohan et al (2012) showed that Bay of Bengal TCs were enhanced when the MJO's convectively enhanced phase was over the Maritime Continent and eastern parts of the Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that the FNISO plays the critical role in triggering the southwest monsoon over the BoB and has unique structure different from boreal winter Madden-Julian Oscillation (MJO) and boreal summer intra-seasonal oscillation (BSISO) (Li et al 2013a). Even though there are some previous studies on the ISO's modulation on the BoB cyclones (Camargo et al 2009;Kikuchi and Wang 2010;Yanase et al 2012;Krishnamohan et al 2012), (2)…”
Section: Dominant Process Associated Fniso To Modulate the Ov Genesismentioning
confidence: 99%
“…This peculiar feature is attributed to the strong modulation by seasonal monsoon circulation (Gray 1968;Yanase et al 2012;Li et al 2013b). It is also identified that BoB TCs are strongly influenced by the intra-seasonal oscillation (ISO) (Camargo et al 2009;Kikuchi and Wang 2010;Yanase et al 2012;Krishnamohan et al 2012). Monsoon onset represents the critical time when the seasonal transition is realized by the intrusion of the first northward-propagating intra-seasonal oscillations (FNISOs) into the central BoB (Li et al 2013a).…”
Section: Introductionmentioning
confidence: 98%